Archaeology - Thomas, David Hurst (Thomson/Wadsworth, 2006)
This new edition by David Hurst Thomas and Robert L. Kelly pairs two of archaeology's most recognized names--with a combined 70 years of experience--for the first time. David Hurst Thomas of the American Museum of Natural History and Robert L. Kelly of the University of Wyoming bring readers a textbook rich with examples drawn from their experiences leading excavations over the past thirty years. A major revision, this fourth edition of ARCHAEOLOGY reflects the most recent research and changes in the field, while covering the core concepts in an exceptionally student-friendly fashion. This edition continues a tradition of academic rigor and engaging writing style that have made this text one of the most well-respected and best-selling texts in the discipline. The new edition is enhanced with full-color photos and a completely new design. The rich array of supplemental resources includes a new companion website, as well as the option to use a new CD-ROM, DOING FIELDWORK: ARCHAEOLOGICAL DEMONSTRATIONS developed by the authors